PEMBERDAYAAN MASYARAKAT : KAMPUNG TUNAGRAHITA MENUJU KAMPUNG MANDIRI DESA KARANGPATIHAN, PONOROGO, INDONESIA - Rosilawati, Yeni; Amalia, Dinar Ayu; Ishak, Aswad (Master of Communication Science Program, Universitas Diponegoro, 2021)
People with intellectual disabilities in Indonesia are vulnerable to discrimination due to lack of information on diseases, treatment, education, public access, and very limited job opportunities. Karangpatihan is a village called Kampung Tunagrahita (Mental Retardation Village) because 86 of its people are suffering from an intellectual disability. A community development program of self-help group (SHG) named Rumah Harapan Karangpatihan Bangkit aims to improve the social and economic capabilities of people with intellectual disabilities in Karangpatihan Village, Ponorogo, Indonesia. The researcher applied a qualitative method in the form of a case study. Data collection techniques used in this study were an in-depth interview with the Head of Karangpatihan Village, managers of Rumah Harapan Karangpatihan Bangkit, and people with intellectual disabilities involved within the program. Secondary data were obtained through the report of the SHG Rumah Harapan Karangpatihan Bangkit and mass media news clipping. This research shows that community development programs are carried out through mentoring mentally retarded citizens through counseling individually and in groups using sign language. Through effective mentoring, mentally disabled people in Karangpatihan Village have life skills, therefore they are able to be independent, have jobs, creative and have income that fullfill their daily needs.